Weather and road capacity - Jensen, Thomas C. (Proceedings from the Annual Transport Conference at Aalborg University, 2014)
The paper presents estimations of the effect of bad weather on the observed speed on a Danish highway section; Køge Bugt Motorvejen. The paper concludes that weather, primarily precipitation and snow, has a clear negative effect on speed when the road is not in hypercongestion mode. Furthermore, the capacity of the highway seems to be reduced in bad weather and there are indications that travel time variability is also increased, at least in free-flow conditions. Heavy precipitation reduces speed and capacity by around 5-8%, whereas snow primarily reduces capacity. Other weather variables such as darkness, frost, wind and fog also have effects, but they are minor and are hard to assess exactly. In general, the effects are less than found in other studies, primarily from North America. The effects are estimated using a two-step procedure. In step 1 the log to travel time is regressed non-parametrically against traffic density and in step 2 the residuals from step 1 are regressed linearly against the weather variables. The choice of a non- parametric method is made to avoid constricting ties from a parametric specification and because the focus here is not on the relationship between traffic flow and speed.